Thematic Classification of Phraseological Units and Proverbs in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article devoted to the study of the thematic classification of phraseological units and proverbs in English and Uzbek languages. A Phraseological unit can be defined as a non-motivated word-group that cannot be freely made up in speech, but is reproduced as a ready-made unit. It is a group of words whose meaning cannot be deduced by examining the meaning of the constituent lexemes. Proverbs allows us to join the way of thinking of another people, understand the originality of the national character, the value system of a certain ethnic group.